Application of information and communication technologies in special libraries in Kerala (India) - Mohamed Haneefa (Library Review Vol. 56 No. 7, 2007 pp. 603-620, 2007)
Purpose - This study was conducted to investigate the application of information andcommunication technologies (ICT) in special libraries in Kerala, India. design/methodology/approach - The following methods were used to collect data for the study: questionnaire survey of librarians and library users, semi-structured interviews with librarians, and observational visits in the libraries. This study was confined only to the automated special libraries in Kerala.Findings : The analyses revealed that though the libraries had hardware, software, and communication facilities to some extent, ICT-based resources and services were not reaching the users to the expected extent. Library automation in special libraries in Kerala was largely commenced during the period 1990-2000. CDS/ISIS was used more in the libraries than any other software. The library catalogue found to be the most popular area for automation. The ICT-based resource used by the largest percentage of the users was the e-mail. Most of the libraries were hampered by lack of funds, lack of infrastructure, and lack of skilled professionals to embark on automation of all library management activities and application of ICT. A good number of the library users were not satisfied with the application of ICT in their libraries and indicated ``inadequate ICT infrastructure'' as their major reason for dissatisfaction. They proposed a variety of measures of formal orientation and training on ICT to become more effective users.Originality/value - The study provides recommendations to enhance library automation and effective and efficient application of ICT.